A Study of Self-Acceptance in Individuals Who Have Experienced Bullying in the Past - Wijaya, Oeij Stevanus; Nurhayati, Siti Rohmah (Universitas Muhammadiyah Surakarta, 2026)
This research is motivated by the rampant bullying that often occurs in education. Bullying behavior that happens during school has a long-term negative impact on the victims. This long-term impact can affect both psychologically and socially. The purpose of this study is to explore the experiences of in-dividuals who have been bullied in the past and to learn how they have engaged in self-acceptance of unpleasant experiences. This research employed a qualitative, phenomenological approach. Data col-lection was carried out through a semi-structured interview with five participants who had a history of experiencing bullying in the past. Data analysis was carried out inductively using interpretative phe-nomenological analysis (IPA). The study results show that there are three processes in self-acceptance, including the initial process, which involves the victim's experience of bullying. The next stage dis-cusses the period after going through bullying behavior, which is associated with the long-term impact of bullying behavior, and the factors that support individuals to bounce back from past experiences. The last stage is the period of self-acceptance, during which individuals feel a positive impact from it. Based on the results of this study, individuals who have accepted themselves can lead more prosper-ous lives, experience more positive emotional regulation, and find greater meaning in their lives.